Competition between Phytophthora infestans effectors leads to increased aggressiveness on plants containing broad-spectrum late blight resistance. - Dennis A Halterman; Yu Chen; Jiraphan Sopee; Julio Berduo-Sandoval; Amilcar Sánchez-Pérez (PLoS ONE, 2010)
BACKGROUND: The destructive plant disease potato late blight is caused by the oomycete pathogen Phytophthora infestans (Mont.) de Bary. This disease has remained particularly problematic despite intensive breeding efforts to integrate resistance into cultivated potato, largely because of the pathogen's ability to quickly evolve to overcome major resistance genes. The RB gene, identified in the wild potato species S. bulbocastanum, encodes a protein that confers broad-spectrum resistance to most P. infestans isolates through its recognition of highly conserved members of the corresponding pathogen effector family IPI-O. IpiO is a multigene family of effectors and while the majority of IPI-O proteins are recognized by RB to elicit host resistance, some variants exist that are able to elude detection (e.g. IPI-O4). METHODS AND FINDINGS: In the present study, analysis of ipiO variants among 40 different P. infestans isolates collected from Guatemala, Thailand, and the United States revealed a high degree of complexity within this gene family. Isolate aggressiveness was correlated with increased ipiO diversity and especially the presence of the ipiO4 variant. Furthermore, isolates expressing IPI-O4 overcame RB-mediated resistance in transgenic potato plants even when the resistance-eliciting IPI-O1 variant was present. In support of this finding, we observed that expression of IPI-O4 via Agrobacterium blocked recognition of IPI-O1, leading to inactivation of RB-mediated programmed cell death in Nicotiana benthamiana. CONCLUSIONS: In this study we definitively demonstrate and provide the first evidence that P. infestans can defeat an R protein through inhibition of recognition of the corresponding effector protein.